Significant Terms of a Mortgage Contract - Ekaterina Nikolaevna Malanina (Сибирское юридическое обозрение, 2011)
This article analyzes the mortgage contract, which has recently been of increasing interest, both in theory and in practice. The author focuses on the essential terms of the mortgage contract, without which it cannot be concluded. The author examines a large number of court decisions and makes a conclusion regarding how these terms should be formulated to conform to the requirements of the law.